A Capability Approach assessment of poverty in the sociopolitical history of South Africa/KwaZulu-Natal. Issue 4 (4th July 2018) - Onwuegbuchulam, Sunday Paul Chinazo
ABSTRACT: The study explores the problem of poverty in the sociopolitical history of South Africa and its negative impact on the majority of the country's African people. The effects of the apartheid government's systematic disenfranchisement of these people are still being felt, constituting a major challenge to the country's democratic government. Notably, extant literature has focused on this problem mostly from an economic conceptual perspective. This study approaches the issue from a Capability Approach perspective. Singling out the country's KwaZulu-Natal province, it argues that poverty in this geographical context is both structural and multidimensional, thus requiring solutions beyond the emphasis on neoliberal economic policies.